THE INFLUENCE OF STUDENT CREATIVITY AND REASON SKILLS ON THE CLASS VIII ALGEBRA TESTING RESULTS OF SMP STUDENTS - Izza Eka Ninggrum; Edi Prajitno (Universitas Ahmad Dahlan, 2018)
The lack of students' creativity and reasoning ability in the mathematics lesson in Grade VIII of State Junior High School 3 Kasihan Bantul (SMP Negeri 3 Kasihan Bantul) of the academic year 2016/2017 is due to frequent students. They are reluctant to ask, even though the explanation of mathematics subject material presented by the teacher has not been understood. This study aims to determine whether or not there the influence of students' creativity and reasoning skills on the algebra test result of year VIII students of SMP Negeri 3 Kasihan Bantul Semester 1 2016/2017 academic year. The population in this research, there are five classes. The samples are taken two classes by random sampling technique and VII C as a first-class and VII D as a second class. Techniques for collecting data use non-test and test. The research instrument is a reasoning skill reasoning test, multiple-choice learning test, and student creativity questionnaire. Instrument-tests include validity tests, different capacity, and reliability. Techniques for analyzing data use prerequisite test analysis consist of normality test, homogeneity test, and hypothesis testing use t-test and LSD test. The results show that (1) Thereof and 6, with on the significant level 5%, df : and . Based on t-test calculation obtained = and (58) = 1,67193 which mean (58) it can be concluded that the creativity of low students has more influence on learning outcomes. (2) Thereof and , with on the significance level 5%, df: and . Based on t-test calculation obtained = dan (58) = 1,67193 that means (60) it can be concluded that high reasoning ability has more influence on learning outcomes. (3)Thereof and , with on the significance level 5%, df: and . Based on the LSD test and t-test the results obtained are low student creativity combined with high reasoning ability influence on learning outcomes